One‐Pot Hydrothermal Synthesis of ZnS Nanospheres Anchored on 3D Conductive MWCNTs Networks as High‐Rate and Cold‐Resistant Anode Materials for Sodium‐Ion Batteries. Issue 8 (20th April 2020) - Fan, Anran; Hou, Tianyi; Sun, Xiaohong; Xie, Dongli; Li, Xin; Zhang, Na; Guo, Jinze; Jin, Shibo; Zhou, Yunmei; Cai, Shu; Zheng, Chunming
Abstract: A 3D conductive network nanostructured composite of ZnS nanospheres anchored on multiwall carbon nanotubes (denoted as ZnS/MWCNTs) is synthesized via one‐pot hydrothermal method as anodes for sodium‐ion batteries. The MWCNTs backbone can form an interconnected network and nano‐sized ZnS spheres are uniformly and closely anchored on the 3D network of MWCNTs. The morphology and microstructures of the electrode materials can be controlled easily by regulating the concentration of thiourea and the amount of MWCNTs. Benefiting from its remarkable architecture, the optimized ZnS/MWCNTs exhibits an excellent cycling performance (397 mA h g −1 after 50 cycles at 100 mA g −1 ) and outstanding rate capability (320 mA h g −1 at 4 A g −1 after 300 cycles ) at room temperatures. Moreover, the optimal ZnS/MWCNTs shows superior electrochemical performance at low temperatures (−10 °C), delivering high reversible capacities of 230 mA h g −1 at 1 A g −1 after 400 cycles. These results make the ZnS/MWCNTs a promising anode material for sodium‐ion batteries, and our findings may offer a feasibility strategy to design other anode materials with good rate and low‐temperature performance. Abstract : It's all about control : The optimized 3D network nanostructure ZnS/MWCNTs composite is prepared via one‐pot hydrothermal method by appropriately regulating the concentration of thiourea and the amount of MWCNTs. The superior rate and cycling performances of the optimized ZnS/MWCNTs at room and low temperature are obtained due to the 3D network structure superiority of ZnS/MWCNTs composite with uniformly distributed ZnS nanospheres and cross‐linked MWCNTs.